2013
DOI: 10.5951/jresematheduc.44.3.0581
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Understandings of Length Measurement: Evaluating a Learning Trajectory

Abstract: This study investigated the development of length measurement ideas in students from prekindergarten through 2nd grade. The main purpose was to evaluate and elaborate the developmental progression, or levels of thinking, of a hypothesized learning trajectory for length measurement to ensure that the sequence of levels of thinking is consistent with observed behaviors of most young children. The findings generally validate the developmental progression, including the tasks and the mental actions on objects that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 55 publications
0
18
0
6
Order By: Relevance
“…The activities in Parkopolis were born from the scientific literature targeting critical STEM skills that predict later school success; such as, patterns [88,89], numeracy and spatial skills [90][91][92], geometry [93], measurement [94], and fractions [87,95]. See Parkopolis and fraction dice designs in Figure 9.…”
Section: Parkopolis: Can We Enrich Public Spaces Even Further By Builmentioning
confidence: 99%
“…The activities in Parkopolis were born from the scientific literature targeting critical STEM skills that predict later school success; such as, patterns [88,89], numeracy and spatial skills [90][91][92], geometry [93], measurement [94], and fractions [87,95]. See Parkopolis and fraction dice designs in Figure 9.…”
Section: Parkopolis: Can We Enrich Public Spaces Even Further By Builmentioning
confidence: 99%
“…The activities in Parkopolis (Figure ) draw on research on early STEM learning, targeting skills such as patterns (Rittle‐Johnson, Fyfe, Loehr, & Miller, ), numeracy and spatial skills (Geary, Bailey, & Hoard, ), geometry (Verdine et al., ), measurement (Szilágyi, Clements, & Sarama, ), and fractions (Fuchs et al., ). Parkopolis also targets domain‐general learning skills like executive functioning (i.e., working memory, cognitive flexibility, and inhibition; Diamond & Lee, ), approaches to learning (i.e., strategic planning, persistence, open‐mindedness, sustained focus, communication, and cooperation; Fantuzzo, Gadsden, & McDermott, ), and fluid reasoning (i.e., logical thinking and problem solving; Green, Bunge, Chiongbian, Barrow, & Ferrer, ).…”
Section: Learning Landscapes Projectsmentioning
confidence: 99%
“…Research in the area of length measure learning trajectories has identified key moments we might reasonably expect among typical students in instruction (Barrett et al, 2012;Sarama & Clements, 2009;Sarama, Clements, Barrett, Van Dine, & McDonel, 2011;Szilágyi, Clements, & Sarama, 2013). For example, Steffe (1991) identified the conceptual ruler that we might expect as early as Grade 3 (about Age 8), which refers to one's ability to mentally iterate units even when not available along a particular object being measured.…”
Section: Implications Theoretical Implicationsmentioning
confidence: 99%